The first hurdle. A guide to searching, applying and interviewing for jobs in sports performance - Ingham, S. (Simply Said, 2020)
Most aspirants are completely unprepared for the job application and interviewing stages. They are either unskilled or don`t know how to show that they have what it takes. This book will help you find the right doors to push and show you how to avoid having them slammed in your face. It will support you in overcoming any hurdles on what could be the most important day in your career.